2020
DOI: 10.1002/ijgo.13281
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal and perinatal characteristics on risk of postpartum chronic hypertension after pre‐eclampsia

Abstract: Objective To assess the prevalence of new‐onset postpartum chronic hypertension (PPCH) after pre‐eclampsia and to determine the factors are associated with it. Methods This study was conducted in a tertiary center in south India, between June 2018 and February 2019, consisting of pre‐eclamptic women who were recruited as part of an ongoing cohort and had completed at least 3 months of postpartum follow‐up. Demographic, medical, and laboratory details were collected. Primary outcome was a diagnosis of new‐onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A total of 524 records were obtained from our second search for recently published primary studies. After excluding records that did not meet our eligibility criteria, a total of 124 primary studies 3 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , …”
Section: Resultsmentioning
confidence: 99%
“…A total of 524 records were obtained from our second search for recently published primary studies. After excluding records that did not meet our eligibility criteria, a total of 124 primary studies 3 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , …”
Section: Resultsmentioning
confidence: 99%
“…With respect to FGR diagnosed outside the context of a pregnancy complicated by pre‐eclampsia, several studies have demonstrated an impaired cardiac adaptation in pregnancies complicated by fetal smallness. In details, lower CO and SV and higher PVR have been demonstrated in normotensive women with a FGR fetus compared to controls, 11,22,24 furthermore differences in terms of CO and PVR were demonstrated between FGR fetuses and small‐for‐gestational age fetuses not fulfilling the Delphi criteria for FGR. More specifically, FGR was shown to be associated with lower CO and higher PVR compared to SGA, furthermore the hemodynamic profile was shown to be similar in mothers diagnosed with a SGA fetus and uncomplicated pregnancies 11,13,20 .…”
Section: The Characteristics Of Maternal Haemodinamics In Pre‐eclamps...mentioning
confidence: 91%
“…Finally, several patients with a history of pregnancy complicated by hypertensive disorders and/or FGR remain at increased risk of developing a range of adverse cardiovascular outcomes long after birth, including hypertension, myocardial infarction and stroke. [21][22][23] In this review, we summarize the current evidence on the maternal cardiac hemodynamics in FGR and pre-eclampsia.…”
mentioning
confidence: 99%
“…Five studies among Chinese, Sudanese, Nigerian, South African, and Ugandan women reported a substantial prevalence of hypertension 6 weeks after pregnancy complicated by PE (28-36%) and GH/PE (26%) (90,109,113,117,119). Three months to 1 year after pregnancy, the prevalence of hypertension among Indian, Cameroonian, Ugandan, Cuban, and Black Dutch women with PE was 15-38%; among Kenyan women with GH/PE prevalence of hypertension was 24% (91,101,102,112,114,120). Prevalence of hypertension was 22% 1 year after pregnancy in Nigerian women with GH, and 61% in women with PE (98).…”
Section: Hypertensionmentioning
confidence: 99%